Dietary fiber: an alternative for nutrition - Villanueva-Flores, Rafael Mauricio (2019)
Dietary fiber consists of a set of elements with different characteristics that provide several physical and chemical properties that determine clear physiological effects. Its consumption provides health benefits; however, it is below the recommended level both in Peru and many countries worldwide. This situation brings an opportunity for the Peruvian food industry to develop mass consumption products with high fiber content.